Digital Financial Services and Financial Inclusion as Drivers of SME Performance: The Moderating Effect of Dynamic Capabilities - Indra Wati (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the impact of Digital Financial Services (DFS) and Financial Inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs), as well as the moderating role of Dynamic Capability in this relationship. The study uses a quantitative approach with a survey design and a sample of 135 MSMEs across various industry sectors. Data was collected through a questionnaire using a Likert scale to measure respondents' perceptions of each variable. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the direct relationships between Digital Financial Services and Performance, Financial Inclusion and Performance, as well as the interaction between Dynamic Capability with both of these variables and Performance. The results of the study show that Digital Financial Services and Financial Inclusion have a significant impact on MSME performance. However, the interaction between Dynamic Capability and Financial Inclusion, as well as between Dynamic Capability and Digital Financial Services, did not show a significant effect on performance. This research provides valuable insights into the factors influencing MSME performance and the need for policies that support the development of digital financial services and financial inclusion to enhance business performance.